Examining Underpricing in Initial Public Offering: Deepening Insights on Non-Financial Information - Rezky, Dikanio Muhammad; Mahri, A. Jajang W.; Utami, Suci Aprilliani (ETIKONOMI, 2025)
Research Originality: The nominal value variable from the prospectus in this study is the novelty, as no previous research has been found. Investors indicate the nominal value as a positive signal from the company to reduce existing information asymmetry. Research Objectives: This study examines the phenomenon of IPO underpricing on the Indonesia Stock Exchange, resulting in suboptimal IPO fund-raising. Research Method: Using a quantitative approach with descriptive and causality designs, the study analyzed 251 companies from 2017 to 2023 through multiple linear regression analysis. Empirical Results: Indonesia has a high IPO underpricing rate of 37.17%. Most IPOs (68.54%) were Shariah-compliant. The reputation of underwriters changed each year, and the free float ratio declined over time. On average, IPOs were oversubscribed by more than 28 times each year. Although COVID-19 affected market sentiment, it did not impact underpricing. The nominal value of IPO stocks varied each year but generally declined. Regression results show Shariah compliance and strong underwriters reduce underpricing, while higher free float, oversubscription, and nominal value increase it. Implications: The implications of this research theoretically support signaling theory and information asymmetry. Practically, this research can be a reference for further researchers, investors, companies, and the government as regulators. JEL Classification: G10, G24, G32, D82